Risk factors for erectile dysfunction in diabetes mellitus: a systematic review and meta-analysis - Dilixiati, Diliyaer; Waili, Alapati; Tuerxunmaimaiti, Aizihaier; Tao, Liwen; Zebibula, Abudureheman; Rexiati, Mulati (Frontiers in Endocrinology, 2024)
Background Previous studies have established that diabetes mellitus (DM) markedly raises the risk of developing erectile dysfunction (ED). Despite extensive investigations, the risk factors associated with ED in diabetic men have yet to be unequivocally determined, owing to incongruent and inconclusive results reported in various studies. Objective: The objective of this systematic review and meta-analysis was to assess the risk factors for ED in men with DM. Methods: A comprehensive systematic review was conducted, encompassing studies published in the PubMed, Scopus and Embase databases up to August 24th, 2023. All studies examining the risk factors of ED in patients with DM were included in the analysis. To identify significant variations among the risk factors, odds ratios (ORs) and their corresponding 95% confidence intervals (CIs) were employed.